Pengaruh Pelatihan, Disiplin Kerja, Dan Kompetensi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja - Celine Keyla Olyfia Silaban (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine and analyze the influence of Training, Work Discipline and Competency on Performance through Job Satisfaction, both partially and simultaneously. This research uses a quantitative approach with descriptive analysis. The data analysis technique used in this research is filling out a questionnaire. In this study, researchers used a questionnaire with a Likert scale which was distributed to 120 respondents or employees. Analysis tools use Partial Least Square Software (Smartpls 4.0). The calculation results show that: (1) the training variable has a positive and significant effect on employee performance; (2) the discipline variable has a positive and significant effect on employee performance; (3) the competency variable has a positive and significant effect on employee performance.